Tourism and Economic Development in ASEAN 1998-2013 - Umara Ardra; Berly Martawardaya (Institute for Economic and Social Research, 2017)
Many countries support government policies to encourage tourism sector, including ASEAN countries, due to an assumption that tourism contributes positively to GDP and poverty reduction. This study investigates that assumption, as well as the correlation between tourism and HDI, by applying panel data regression to eight ASEAN countries (Brunei Darussalam, Indonesia, Laos Singapore, Malaysia, Thailand, the Philippines, and Vietnam,) during 1998–2013. We found that the number of international tourist arrivals as a proxy variable for tourism have a significant and positive correlation with poverty reduction. Tourism is also proven to increase GDP per capita (albeit in a smaller magnitude) and increase HDI (in an even smaller scale). These findings confirmed our hypothesis on the positive effects of tourism. It is recommended that the tourist promotion is continued while studying the best practices to strategically develop the tourism sector in order to strengthen the positive correlation.